Neural Processing of Facial Identity and Emotion in Infants at High-Risk for Autism Spectrum Disorders - Fox, Sharon E.; Wagner, Jennifer; Shrock, Christine L.; Flusberg, Helen T.; Nelson, Charles A. (Frontiers in Human Neuroscience, 2013)
Deficits in face processing and social impairment are core characteristics of autism spectrum disorder. The present work examined 7 month-old infants at high risk for developing autism and typically developing controls at low risk, using a face perception task designed to differentiate between the effects of face identity and facial emotions on neural response using functional Near Infrared Spectroscopy (fNIRS). In addition, we employed independent component analysis (ICA), as well as a novel method of condition-related component selection and classification to identify group differences in hemodynamic waveforms and response distributions associated with face and emotion processing. The results indicate similarities of waveforms, but differences in the magnitude, spatial distribution, and timing of responses between groups. These early differences in local cortical regions and the hemodynamic response may, in turn, contribute to differences in patterns of functional connectivity.